2013
DOI: 10.1103/physreva.88.043801
|View full text |Cite
|
Sign up to set email alerts
|

Controlling multimode coupling by boundary-wave scattering

Abstract: We show that coupling among multiple resonances can be conveniently introduced and controlled by boundary wave scattering. We demonstrate this principle in optical microcavities of quasicircular shape, where the couplings of multiple modes are determined by the scattering from different harmonic boundary deformations. We analyze these couplings using a perturbation theory, which gives an intuitive understanding of the first-order and higher-order scattering processes. Different scattering paths between two bou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…When the system is perturbed, the eigenmodes of the original, unperturbed system become coupled. In optics, for example, the coupling can be introduced by matter-mediated interaction in cavity quantum electrodynamics [1,2], by nonlinearity in multimode lasers [3], and by linear scattering from a local defect or a gradual boundary deformation in optical waveguides [4] and microcavities [5][6][7][8]. In addition, rotation causes a minute change of the refractive index [9], which leads to the mixing of standing-wave resonances in optical microcavities [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…When the system is perturbed, the eigenmodes of the original, unperturbed system become coupled. In optics, for example, the coupling can be introduced by matter-mediated interaction in cavity quantum electrodynamics [1,2], by nonlinearity in multimode lasers [3], and by linear scattering from a local defect or a gradual boundary deformation in optical waveguides [4] and microcavities [5][6][7][8]. In addition, rotation causes a minute change of the refractive index [9], which leads to the mixing of standing-wave resonances in optical microcavities [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It applies both in and beyond the "dead zone" and takes into account the phase of the coupling constant. Since ψ + and ψ − are quasi-degenerate, their mutual coupling is much stronger than that with any resonance farther away in frequency [27,28]. Therefore, it is a good approximation to write their wave function as ψ(Ω) ≈ a + (Ω)ψ + + a − (Ω)ψ − when discussing how they evolve towards the CW and CCW resonances with rotation.…”
Section: Arxiv:14045289v1 [Physicsoptics] 21 Apr 2014mentioning
confidence: 99%
“…For example, scattering from m 0 to m 0 − ν is enhanced when the frequencies of the WG modes with m 0 and m 0 − ν are well aligned. The spectral overlap can make higher-order scattering processes significant and even comparable to the lower-order ones [27].…”
mentioning
confidence: 99%
“…Hence, introducing harmonic perturbations to the cavity boundary shape may be used as a "knob" to tune the far-field emission pattern. In previous studies [26,27], we showed theoretically that the emission patterns of deformed microcavities can be varied significantly with the first-order or the second-order perturbations; however, many of these numerical examples required a fine-tuning of the cavity shape, which is difficult to realize experimentally. In this Letter, we use higher-order scattering, which is more tolerant to the limited accuracy of experimental fabrication than lower-order scattering (see the Supplemental Material [28]).…”
mentioning
confidence: 99%